Einstein Before Israel : Zionist Icon or Iconoclast? - Rosenkranz, Ze'ev (Princeton University Press, 2011)
"A vivid sense of strangeness": Einstein's path to the Zionist movement -- A different kind of nationalism: Einstein's induction and mobilization into the Zionist movement -- The "prize-winning ox" in "Dollaria": Einstein's fundraising trip to the United States in 1921 -- Secular pilgrim or Zionist tourist?: Einstein's tour of Palestine in 1923 -- The "botched university": Einstein's involvement in the Hebrew University, 1924-1929 -- "A genuine symbiosis": Einstein on the 1929 clashes in Palestine -- The "bug-infested house": Einstein's involvement in the Hebrew University, 1930-1933